UPAYA MENINGKATKAN MINAT BELAJAR SISWA DENGAN METODE STORYTELLING PADA MATA PELAJARAN SKI DI MADRASAH IBTIDAIYAH - Barotut Takiyah; Uswatun Khasanah; Tsaniatus Soraya; Rini Meliana; Auliya Aliffiyana; Dwi Putri; Dian Rif'iyati (STKIP Subang, 2026)
This study aims to examine the implementation of the storytelling method and its effect on students' learning interest in Islamic Cultural History (SKI) learning. The research method used is a literature study with a descriptive qualitative approach. Data were collected through reviewing various written sources such as books, scientific journals, and previous research relevant to the topic. The results of the study indicate that the storytelling method in SKI learning can be implemented systematically through apperception activities, communicative storytelling, and active student involvement through questions and discussions. A two-cycle reflective approach further revealed that iterative improvements including the use of visual media, shortened narrative duration, and role-play integration significantly enhanced student engagement. Based on the analyzed sources, the storytelling method has been proven to increase students' learning interest, as indicated by improved attention, participation, and enthusiasm in learning. In addition, this method helps students understand the material more deeply and improves their memory of historical events and moral values contained in the lessons. In conclusion, the storytelling method is an effective learning strategy to enhance students' learning interest in SKI and to create a more engaging and meaningful learning environment.